A Two-Step Right Hepatic Lobectomy with Portal Vein Ligation for Large Hepatocellular Carcinoma: Rapid Induction of Left-Lobe Regeneration and Clinicopathologic Correlation - Ding, Xianzhong; Carrasco-Avino, Gonzalo; Thung, Swan N.; Roayaie, Sasan (Seminars in Liver Disease, 2013)
The patient is a 56-year-old man with a long history of chronic hepatitis B, who developed multiple hepatocellular carcinomas in the right lobe with invasion of the right anterior portal vein. There was no evidence of tumor involvement in the left lobe or in extrahepatic organs. Given that the patient had advanced hepatocellular carcinoma associated with gross vascular invasion, a two-step liver resection procedure was performed with right portal vein ligation during the first operation and a subsequent right lobectomy of the liver. The stage I portal vein ligation induced a rapid growth of the left and caudate lobes of the liver with a volume increase from 201 to 405.2 mL in 9 days associated with a slight shrinkage of the tumor nodules. The subsequent right lobectomy was successfully done with a complete removal of tumor nodules and a well-compensated liver function. Postoperatively the patient was complicated with Staphylococcus aureus peritonitis, which was controlled eventually. Biopsy of the left lobe of liver revealed severe small- and medium- droplet steatosis, in addition to regenerative changes. In summary, right portal vein ligation with in situ splitting of the liver allows the surgeon to proceed with hepatic resection in cases where portal vein embolization is technically not possible. The increased risk of morbidity and mortality certainly must be weighed when contemplating this approach and is discussed in this report.
Keywords: portal vein ligation; hepatocellular carcinoma; two-step hepatic resection; liver regeneration; chronic hepatitis B; gross vascular invasion